Topografisk analys av sätthärdat stål - Svensson, Isak; Fajersson, Theo (My University, 2023)
The background for this thesis project was that Parker Hannifin AB studied the surface structure of case-hardened steel. Parker identified different deformations on the surface, which they referred to as ”höghus” (skyscrapers) and ”grantoppar” (forest) due to their resemblance to these structures. Curious about the composition and formation of these deformations, Parker initiated this thesis project. The goal with this project is to determine how theese deformations affect the surface structure of the steel and whether it is necessary to post-process the surface. To examine the surface structure, laboratory equipment such as a scanning electron microscope (SEM) and an optical 3D profiling microscope were utilized at RISE in Mölndal. The project started with grinding the surfaces of material samples, which were provided by Parker. The samples were ground using five different grit numbers to study if different surface finishes affected the results. All samples were also studied under an optical 3D profiling microscope before and after they were heat treated to ensure that the deformations Parker found appeared. This was done to eliminate different variables from the heat treatment process and to find out how these ”skyscrapers” and ”forest” occur. All of the samples were also analyzed in SEM to get a better understanding of the surface. An EDS analysis was also conducted for all samples to determine the chemical structure of the ”skyscrapers” and ”forest”. The result of the study was that standard case-hardening leads to the formation of ”skyscrapers” and ”forest”. The ”skyscrapers” are most likely residual products from the quenching oil used in the case-hardening process. This conclusion comes from the EDS analysis, which shows that most ”skyscrapers” consist of coal, sulfur, silicon, and several other substances that can be found in quenching oil. The ”forest” consists of iron surrounded by different oxides. During analyses in SEM, a Turing pattern could be observed for the ”forest”. This means that the ”forest” could be simulated using a mathematical model. The conclusion for the ”forest” is that the oxides which form on the surface in the furnace grow faster than the iron. This means the iron must squeeze through the oxides, which creates the ”forest” pattern.
Keywords: Sätthärdning; Stål; Svepelektronmikroskop (SEM); Ytstruktur; Slipning; EDS; Turing-mönster; Härdolja; Oxider